Counseling Service Activities to Improve Guidance and Counseling Supervision in Vocational High Schools - Nakhma’Ussolikhah Nakhma’Ussolikhah; Chandrisya Yuvie Zhaffirly; Muhammad Rizal Muttaqin; Megananda Prichillia; Muhammad Luthfi Ansori; Muhammad Yoga Nugraha (Journal of Education and Teacher Training Innovation, 2023)
Differences in the perceptions of guidance and counseling teachers and subject teachers cause student learning activities to be less than optimal. The limitations of guidance and counseling teachers in providing classical services have an impact on the potential for academic activities in schools. The aim of this research is to improve the performance of guidance and counseling teachers by supervising guidance and counseling activities. Guidance and counseling supervision activities are to develop the potential of guidance and counseling teachers so that they can carry out counseling services effectively and efficiently. The general implementation is to conduct direct contact sessions with the individual being analyzed over several time periods. This research approach uses qualitative methods using a phenomenological approach . The data collection instrument technique uses periodic interview and observation instruments . The research location was carried out at SMK N 2 Kuningan . S main subject in study This that is consisting of Supervisors , Principals and subject Guidance Teachers . Data analysis techniques use analytical techniques descriptive . The results of this research illustrate that BK supervision activities are running well based on the school's vision and mission. ISO limitations provide changes to the service instrument. The implementation of BK supervision with individual counseling services is going well. Collaboration between students, guidance and counseling teachers, supervisors is carried out in accordance with work program guidelines and instruments.